2004
DOI: 10.1051/jp4:2004122025
|View full text |Cite
|
Sign up to set email alerts
|

Étude thermodynamique du polymère super absorbant X10 vis–à–vis de l’eau vapeur

Abstract: Abstract. The organic polymers super absorbents present values of specific surface lower than 2m 2 /g. The isobars of adsorption of water vapor on studied polymer are of type III at ambient temperature with the hysterisis phenomena. For temperatures lower than ambient, the isobars become deformed because of an effect of chains. This type of polymer is characterized by a multi-layer adsorption which occurs before the full-course one is complete. During reactions of adsorption, the polymer undergoes rearrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…6), as that was obtained by the method of specific surface measurements of the product, which showed that the polymer is nonporous and present a weak surface (2.1 m 2 / g). 14 The analysis of the composition images obtained by retroimagery made it possible to conclude that our sample is homogeneous.…”
Section: Discussionmentioning
confidence: 96%
“…6), as that was obtained by the method of specific surface measurements of the product, which showed that the polymer is nonporous and present a weak surface (2.1 m 2 / g). 14 The analysis of the composition images obtained by retroimagery made it possible to conclude that our sample is homogeneous.…”
Section: Discussionmentioning
confidence: 96%